DETERMINAN KETEPATAN WAKTU DALAM PUBLIKASI LAPORAN KEUANGAN DENGAN OPINI AUDIT SEBAGAI VARIABEL MODERASI - Riski Famiyanti; Hero Priono (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2025)
Introduction: This study aims to examine the effect of auditor opinion on the relationship between profitability, liquidity, company size, and financial reporting period. Furthermore, this study aims to determine the impact of these factors on the accuracy of financial statements. Methods: This research is a quantitative study with an explanatory method by collecting secondary data from 92 manufacturing and non-manufacturing companies listed on the Indonesia Stock Exchange (IDX) in the 2019-2023 period. The sampling technique in this study used purposive sampling method, so that the sample used in this study was 58 companies that met the criteria. The data analysis used is logistic regression analysis and mode regression analysis (MRA) using SPSS software version 26. Based on the partial test results.Results: the results show that profitability is proven to have a positive and significant effect on the financial reporting time series. Meanwhile, liquidity and company size are not proven to have a significant effect on the time series of financial report publication. Simultaneously profitability, liquidity, and company size affect the timeliness of financial report submission. The results of MRA testing show that auditor opinion cannot moderate the relationship between profitability, liquidity, and company size on the timeliness of report submission. Keywords: Profitabilitas, Likuiditas, Ukuran Perusahaan, Opini Audit, Ketepatan Waktu, Laporan Keuangan